Treatment of COVID-19 in Hemodialysis Patients Using Traditional Chinese Medicine: A Single-Center, Retrospective Study - Huang, Wei; Jiang, Bo; Luo, Jinli; Luo, Meng; Ding, Xiaoming; Yang, Qian; Zhao, Lin-Hua; Sun, Qin-Guo; Tong, Xiao-Lin (Frontiers in Pharmacology, 2022)
Background: To explore the effect of combining traditional Chinese medicine (TCM) and Western medicine in hemodialysis patients with coronavirus disease 2019 (COVID-19). Methods: This study was conducted from January 27, 2020 to March 17, 2020 in Wuhan Third Hospital Guanggu Branch, Wuhan, China. Fifty-three patients were included and divided into a control group (CG), which received Western medicine and a combined treatment group, which received TCM and Western medicine (TG). Clinical and laboratory data, TCM symptom scores, and chest computed tomography results were extracted and compared between the two groups. Results: The TG included 21 (67.7%) men and 10 (32.3%) women with a mean age of 61.02 (standard deviation [SD] 15.07, range 26–89) years. The mean dialysis duration in the TG was 49 (SD 31) months. Of all patients in the TG, 27 (87.1%) had fatigue, 18 (58.1%) had dry cough, 16 (51.6%) had anorexia, 11 (35.5%) had dyspnea, and 11 (35.5%) had fever. The CG included 14 (63.6%) men and 8 (36.4%) women with a mean age of 61.45 (SD 13.78, range 36–84) years. The mean dialysis duration in the CG was 63 (SD 46) months. Of all patients in the CG, 21 (95.5%) had fatigue, 12 (54.5%) had dry cough, 17 (77.3%) had anorexia, 12 (54.5%) had dyspnea, and 7 (31.8%) had fever. After treatment, the TCM symptom scores of the two groups decreased; the anorexia scores were lower in the TG than in the CG (p<0.05). After treatment, albumin increased and D-dimer, C-reactive protein, and lactate dehydrogenase levels decreased in the TG. The d-dimer levels were lower and the albumin level was higher in the TG than in the CG after treatment (p<0.05). The cure rate was higher, and the mortality rate was lower in the TG than in the CG (p<0.05). Conclusions: A combination of TCM and Western medicine in hemodialysis patients with COVID-19 could relieve symptoms and help recovery. Further evidence from larger randomized controlled trials is needed to confirm our results.